Enhancing polyhydroxalkanoate (PHA) production from phenol through fermentation strategies: a review - Sabri, Izzati; Mohd Yusoff, Mohd Zulkhairi; Nor Muhammad, Nor Azlan; Ho, Li Sim; Ramli, Norhayati (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Microbial conversion offers a promising solution to two environmental challenges, phenol and plastic pollutions, via the transformation of phenol into bioplastics, specifically polyhydroxyalkanoate (PHA). Synthetic plastics are widely used across various sectors; however, their non-biodegradable nature and extensive daily use significantly contribute to environmental deterioration. Similarly, phenol, an important industrial material, is often released into the environment through inadequately treated effluents. Phenol is toxic even at low concentrations and may lead to severe environmental and health problems if not properly managed. Microorganisms not only degrade phenol into non-harmful compounds, facilitating its removal from the environment, but they also accumulate intracellular PHA, providing a biodegradable alternative to synthetic plastics. However, phenol’s toxicity at high concentrations can inhibit this process, leading to cell death. This review explores various fermentation strategies aimed at enhancing PHA production while addressing phenol toxicity. These strategies include the use of mixed microbial community (MMC), acclimatization to increasing phenol concentrations, feast-and-famine strategies, co-substrate supplementation, and substrate feeding strategies. An integrated approach would be more effective in overcoming phenol toxicity, leading to complete phenol degradation and improved PHA accumulation. However, these strategies must be tailored to the capabilities of microorganisms in adapting to and utilizing phenol as feedstock. Overall, these fermentation strategies have the potential to improve the management of plastic waste and phenol-contaminated wastewater, contributing to a more sustainable future.